2006
DOI: 10.1116/1.2165661
|View full text |Cite
|
Sign up to set email alerts
|

Texture of Ru columns grown by oblique angle sputter deposition

Abstract: Ru films were sputter deposited on native oxide p-Si͑100͒ substrates under normal incidence and oblique angle incidence with and without substrate rotation. We characterized the crystalline texture and morphology of the Ru films by x-ray diffraction, transmission electron microscopy, and scanning electron microscopy. For the case of normal incidence, a smooth, uniform surface layer was observed, and pole figure analysis showed coexisting ͕1010͖, ͕0002͖, and ͕1011͖ normally oriented textures. For oblique angle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…This showed that the fiber texture dispersion angle has a scaling behavior. This fiber structure of vertical nanorods was confirmed by x-ray pole figures (Morrow et al 2006). An individual nanorod was examined by TEM, and the TEM diffraction pattern revealed single-crystal structure in the individual nanorod.…”
Section: Ru Nanorods On An Amorphous Substratesupporting
confidence: 53%
“…This showed that the fiber texture dispersion angle has a scaling behavior. This fiber structure of vertical nanorods was confirmed by x-ray pole figures (Morrow et al 2006). An individual nanorod was examined by TEM, and the TEM diffraction pattern revealed single-crystal structure in the individual nanorod.…”
Section: Ru Nanorods On An Amorphous Substratesupporting
confidence: 53%
“…18 In summary, the micrographs in Fig. 1 and 2, for room temperature growth of Ta, Cr, and Al rods, as well as Ta grown at T s = 300-993 K. The plot also includes values from previously reported studies by various researchers on Ti, 40 Ni, 41 W, 42 Cu, 43 Co, 6 Ru, 44 and Al. Figure 2 shows the plan-view ͓͑a͒-͑c͔͒ and crosssectional ͓͑d͒-͑f͔͒ SEM images from Ta nanorods grown on flat substrates at T s = 473, 773, and 973 K, respectively.…”
Section: Resultsmentioning
confidence: 84%
“…However, the intensity of (002) diffraction peak does not increase as the FWHM decreases among the samples, denoting a complex relationship. This might be due to tilted texture observed in some GLAD nanostructures where crystal planes tend to follow the flux direction [17][18][19]. As can be seen in Table 1 and Fig.…”
Section: Morphological Properties and Crystallinity Of Azo Nanostructmentioning
confidence: 87%
“…Similarly, GLAD Si nanostructures of different shapes (pillars, oblique, helix), which were produced by different substrate rotation speeds at constant deposition angle of 83°, were also reported to have different film densities. Change in the layer densities of our GLAD AZO nanostructures may be explained by a competitive growth dynamics of different crystalline orientations/phases [13][14][15][16]. Although the same deposition angle is expected to provide a same deposition rate (average number of particles coming to the substrate in time), rotation speed can influence the growth rate at a local point.…”
Section: Morphological Properties and Crystallinity Of Azo Nanostructmentioning
confidence: 95%
See 1 more Smart Citation